2020
DOI: 10.1111/maps.13473
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and oxygen isotopic compositions of calcium‐aluminum‐rich inclusions in primitive CO3.0‐3.1 chondrites

Abstract: The petrologic and oxygen isotopic characteristics of calcium-aluminum-rich inclusions (CAIs) in CO chondrites were further constrained by studying CAIs from six primitive CO3.0-3.1 chondrites, including two Antarctic meteorites (DOM 08006 and MIL 090010), three hot desert meteorites (NWA 10493, NWA 10498, and NWA 7892), and the Colony meteorite. The CAIs can be divided into hibonite-bearing inclusions (spinel-hibonite spherules, monomineralic grains, hibonite-pyroxene microspherules, and irregular/nodular obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 101 publications
(239 reference statements)
0
4
0
Order By: Relevance
“…review by Rubin & Ma 2017). CAI abundance in the most primitive (CO3) chondrites is ∼ 1.5 area per cent 1 with an average CAI size of 98.4 ± 54.4 𝜇m (Zhang et al 2020). Melilite-rich inclusions and spinel-pyroxene CAIs comprise 80-100 percent of the total CAIs for each chondrite; Zhang et al argued that the spinel-pyroxene CAIs in these and more processed meteorites are alteration products derived from melilites and found that a subset of fluffy melilites were composed of loosely aggregated < 15𝜇m-sized melilite grains.…”
Section: Oxygen-rich Candidates: Melilite and Hibonitementioning
confidence: 99%
See 1 more Smart Citation
“…review by Rubin & Ma 2017). CAI abundance in the most primitive (CO3) chondrites is ∼ 1.5 area per cent 1 with an average CAI size of 98.4 ± 54.4 𝜇m (Zhang et al 2020). Melilite-rich inclusions and spinel-pyroxene CAIs comprise 80-100 percent of the total CAIs for each chondrite; Zhang et al argued that the spinel-pyroxene CAIs in these and more processed meteorites are alteration products derived from melilites and found that a subset of fluffy melilites were composed of loosely aggregated < 15𝜇m-sized melilite grains.…”
Section: Oxygen-rich Candidates: Melilite and Hibonitementioning
confidence: 99%
“…Hibonite is less plausible because the fits are poorer, fewer than 4.8 per cent of CAIs in meteorites are hibonite (and grossite; ∼CaAl 4 O 7 )bearing (Zhang et al 2020), with the metamict form being relatively rare and other hibonites have weaker overtones which do not occur at 6.9 𝜇m, and hibonite bands are bands are 5-30 times weaker than the melilite feature (see Appendix A3 and Bowey & Hofmeister 2005).…”
Section: Oxygen-rich Candidates: Melilite and Hibonitementioning
confidence: 99%
“…review by Rubin & Ma 2017). CAI abundance in the most primitive (CO3) chondrites is ∼1.5 area per cent 1 with an average CAI size of 98.4 ± 54.4 μm (Zhang et al 2020). Melilite-rich inclusions and spinel-pyroxene CAIs comprise 80-100 per cent of the total CAIs for each chondrite; Zhang et al argued that the spinel-pyroxene CAIs in these and more processed meteorites are alteration products derived from melilites and found that a subset of fluffy melilites were composed of loosely aggregated <15 μm-sized melilite grains.…”
Section: Oxygen-rich Candidates: Melilite and Hibonitementioning
confidence: 99%
“…Hibonite is less plausible because the fits are poorer, fewer than 4.8 per cent of CAIs in meteorites are hibonite (and grossite; ∼CaAl 4 O 7 )bearing (Zhang et al 2020), with the metamict form being relatively rare and other hibonites have weaker overtones which do not occur at 6.9 μm, and hibonite bands are bands are 5-30 times weaker than the melilite feature (see Appendix A3 and Bowey & Hofmeister 2005).…”
Section: Oxygen-rich Candidates: Melilite and Hibonitementioning
confidence: 99%